2002
DOI: 10.1002/1521-4095(20021016)14:20<1480::aid-adma1480>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Doped Polyaniline

Abstract: Polyaniline/multiwalled carbon nanotube composite films have been fabricated. It is shown that the nanotubes affect the free N–H environment and quinoid units along the polymer backbone. A 10‐fold increase in conductivity is observed and elemental analysis indicates that the nanotubes compete with chloride ion during HCl doping (see Figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
430
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(457 citation statements)
references
References 0 publications
24
430
1
2
Order By: Relevance
“…Therefore, it is reasonable to expect that CNTs and PAni should interact favorably together. In fact it has been reported that CNTs can act as PAni dopants, interacting with both N-H bonding and also quinoid rings on the PAni backbone to increase PAni conductivity [60]. Site-selective interactions between the quinoid ring on the PAni backbone and MWNTs have been reported to facilitate charge transfer between the two components [31].…”
Section: Composite Characterizationmentioning
confidence: 99%
“…Therefore, it is reasonable to expect that CNTs and PAni should interact favorably together. In fact it has been reported that CNTs can act as PAni dopants, interacting with both N-H bonding and also quinoid rings on the PAni backbone to increase PAni conductivity [60]. Site-selective interactions between the quinoid ring on the PAni backbone and MWNTs have been reported to facilitate charge transfer between the two components [31].…”
Section: Composite Characterizationmentioning
confidence: 99%
“…The mixed solution was stirred at room temperature for 3 h. MWNTs in the mixed solution were dispersed by a sonicator. 21),28) The solution was then spin-coated at 2,000 rpm for 20 s on substrates of two types. Corning 1737 glass substrates were used to measure crystallinity, as well as optical and electrical properties.…”
Section: Methodsmentioning
confidence: 99%
“…21) For the fabrication of electronic circuits, micro-patterning is a commonly used process. However, the conventional dry etching process is accompanied by the generation of physical defects, degradation of properties, and pollution from hazardous materials.…”
Section: )20)mentioning
confidence: 99%
“…Fig.6, described as the electronic-like band, is considered to be a measure of the degree of delocalization of electrons and thus it is characterized peak of PANI [13]. The band at 1569.95 cm …”
Section: 2ftir Spectramentioning
confidence: 99%